Subcutaneous fast-acting insulin analogues, alone or in combination with long-acting insulin, versus intravenous regular insulin infusion in patients with diabetic ketoacidosis: protocol for an updated systematic review and meta-analysis of randomised trials - Beng Leong Lim; Wei Feng Lee; Berlin Lee; Yan Ee Lynette Chung; Kee Vooi Loo (BMJ Open)
Introduction Diabetic ketoacidosis (DKA) is traditionally managed using intravenous regular insulin infusion (RII) in intensive care unit (ICU)/high dependency unit (HDU). Subcutaneous fast-acting insulin analogues (FAIAs) may help to manage DKA outside ICU/HDU. Furthermore, combining subcutaneous long-acting insulin (LAI) with subcutaneous FAIAs may accelerate ketoacidosis resolution. The latest (2016) Cochrane review was inconclusive regarding subcutaneous FAIAs versus intravenous RII in DKA. It was limited by small sample sizes, unclear risk of bias (RoB) in primary trials and did not examine subcutaneous FAIAs with subcutaneous LAI versus intravenous RII in DKA. We report the protocol for an updated meta-analysis on the safety and benefits of subcutaneous FAIAs with/without subcutaneous LAI versus intravenous RII in DKA.Methods and analysis We will search Medline, Embase, CINAHL and Cochrane Library, from inception until December 2022, without language restrictions, for randomised trials on subcutaneous FAIAs with/without subcutaneous LAI versus intravenous RII in DKA. We also search ClinicalTrials.gov, ClinicalTrialsRegister.eu and reference lists of included trials. Primary outcomes include all-cause in-hospital mortality, time to DKA resolution, in-hospital DKA recurrence and hospital readmission for DKA post-discharge. Secondary outcomes include resource utilisation and patient satisfaction. Safety outcomes include important complications of DKA and insulin. Reviewers will extract data, assess overall RoB and quality of evidence using Grading of Recommendations, Assessment, Development and Evaluation. We will assess statistical heterogeneity by visually inspecting forest plots and the I2 statistic. We will synthesise data using the random-effects model. Predefined subgroup analyses are: mild versus moderate versus severe DKA; age <20 vs ≥20 years; pregnant versus non-pregnant; infective versus non-infective DKA precipitating cause; subcutaneous FAIAs alone versus subcutaneous FAIAs and subcutaneous LAI; and high versus low overall RoB. We will also perform trial sequential analysis for primary outcomes.Ethics and dissemination Ethics board approval is not required. Results will be disseminated through publication in a peer-reviewed journal.PROSPERO registration number CRD42022369518.